Long-term effect of the absence of a companion robot on older adults: A preliminary pilot study - Yamazaki, Ryuji; Nishio, Shuichi; Nagata, Yuma; Satake, Yuto; Suzuki, Maki; Kanemoto, Hideki; Yamakawa, Miyae; Figueroa, David; Ishiguro, Hiroshi; Ikeda, Manabu (Frontiers in Computer Science, 2023)
Robotic assistive technology for frail older adults has drawn attention, along with raising ethical concerns. The ethical implications of a robot’s usage have been characterized in the literature as detrimental, such as emotional deception, unhealthy attachment, and reduced human contact from a deontological perspective. These concerns require practical investigations, although the long-term influence of robot usage on older adults remains uncertain. Our longitudinal study aimed to investigate how older adults with cognitive decline could be affected by a robot for communication used in their homes and how this situation could be reflected in possible emotional attachment to the robot i.e., emotional distress from the robot being taken away once they have become attached to it. We selected 13 older adults living alone and set up a humanoid robot in their homes for interaction at any time during a period of one to four months. Questionnaire results indicated participants had a close attachment to the robot even after it was taken away. Interviews revealed that participants became distressed in their life without the robot; however, despite the distress of loneliness, participants made their relationships with the robot meaningful and were satisfied in the memory of having kept its company. The results raised new questions for further investigation into issues that should be addressed and potential factors affecting the user’s adaptation processes. Regarding the consequences from the use of a companion robot, it is important to evaluate positive aspects of the robot’s usage including its emotional support lasting after it is no longer available and other effects on the users. Accordingly, we emphasize the significance of real-world exploration into effects on the users as well as theoretical reflection on appropriate robot usage.